Device for integrated diagnostics of mining machines triboelements - Gorlov I (EDP Sciences, 2021)
This article presents the results of multiple-conditions wear-resistance tests for the antifriction bearings that are used in a milling tool. The test was performed on a one-fifth milling tool model. The tests were divided into three stages. The first testing stage included tests of a model with a new undamaged bearing. The second stage included tests of a model with a bearing that is worn out by approximately 50%. The third stage included tests of a model with a completely worn out antifriction bearing. Along with vibroacoustic tests, we measured the temperatures of the tested triboelement. In this article, we provide amplitude-frequency values of vibroacoustic signals recorded during the tests of a model with an undamaged antifriction bearing, a bearing with 50% worn-out extent, and 100% worn-out bearing. Appropriate resistance levels of complex machine elements cannot be achieved without systems of triboelements condition control. We suggest attaching temperature and vibroacoustic sensors to the critical elements of a peat winning machine that provide data for integral analysis of triboelemets condition and prevent failures when damage is recorded. Integral analysis of the technical condition of the main triboelements will allow performing the highly precise prognosis of the remaining life of a peat-winning machine, thus preventing failures in peat mining seasons.